Dampak Literasi Keuangan dan Financial Experience Generasi Z terhadap Penggunaan PayLater di E-Commerce - Desvita Mahanani, Andestia; Alifia Nauli, Deva; Alvaro Sihombing, Juanh (Teewan Journal Solutions, 2025)
This study aims to analyze the impact of financial literacy and financial experience of Generation Z on Paylater in E-commerce. The method used is a qualitative approach with phenomenological techniques, involving 120 respondents from the University of Persada Indonesia Y.A.I. Data were collected through observation, interviews, and documentation. The results of the study indicate that financial literacy has a significant influence on the decision to use Paylater services, where respondents with a good level of literacy are more careful in using this service. On the other hand, financial experience does not show a significant influence. This study concludes that increasing financial literacy can help generation Z in making wiser financial decisions. There is a need for development to create better financial literacy education programs specifically aimed at Generation Z to increase their understanding of the risks and benefits of digital financial services such as Paylater. This is very important to minimize the possibility of incurring consumer debt and also to encourage wiser financial decisions in this digital age.